Building infrastructures for inclusive regeneration. (October 2021) - Slade, Jason; Inch, Andy; Crookes, Lee
Abstract: This paper explores the foundational role of physical infrastructure in making inclusive, community-led regeneration possible. It does this through documenting three years of engaged research on participatory planning, conducted in Westfield, a community in Sheffield, UK, which experiences 'multiple deprivation'. The research looked to support community-led planning efforts taking place under the auspices of the Big Local regeneration programme and afforded significant insight into the combined impacts of austerity and ideologically driven community development initiatives for people trying to make positive change in their communities. Our principal contributions are twofold: firstly, a theoretical contribution, on the role of physical infrastructure and how it is understood in making certain kinds of community development possible and impossible; secondly, the application of this theoretical insight to a concrete case, Westfield's pub-turned-community-centre, Com.unity. We conclude by arguing for the critical importance of 'the publicness of public things', and the need for a fundamental reimagining of the roles and responsibilities of both the state and communities in valuing and investing in the infrastructures that make inclusive urban regeneration possible . Highlights: Social infrastructure offers a lens for rethinking people- and place-based regeneration. Social infrastructure helps bridge distinctions between physical and social planning. Public-ness of social infrastructure is dynamic and contingent upon political context. Community ownership of social infrastructure is no guarantee of greater inclusivity. Social infrastructure can strengthen or undermine community-led development.